HOKBEN JABABEKA'S BUSINESS STRATEGY IN CREATING CUSTOMER SATISFACTION - Agustini Tanjung; Soni Suardi (SEAN Institute, 2023)
The development of the industry in the food industry is growing rapidly. Especially in the food industry which has long faced the free market. Price, product quality, and service quality are the most important things in a business to get customer satisfaction. This type of research is a quantitative method. The research approach used in this research is descriptive analysis using questionnaire data with a sample of 96 respondents. The sampling technique used was non-probability sampling with a purposive sampling method. The statistical analysis used in this study is the validity and reliability test of the classic assumption test, regression analysis, hypothesis testing using the t test, F test and analysis of the coefficient of determination. T test results of the price variable t value obtained t-count = 2,690, product quality variable obtained t-count = 4,481, service quality variable obtained t-count 2,340. While the table obtained using the alpha value (α = 5%, a value of 1.989 was obtained). T value is greater than the table value which means that there is a partially and significantly positive effect between price, product quality, service quality on satisfaction. The results of the f test statistics obtained the calculated f value of 31.202. (α = 5%, f table = 2.70). The results show that the f count is greater than the f table (31,202 > 2.70), with a significant value (0,000 < 0.05) which means that there is a simultaneous and significant positive effect between price, product quality, service quality on customer satisfaction. The coefficient of determination (R2) R-square value of 0.504, this means that the price, product quality, service quality variables affect customer satisfaction as much as 50.4%, the rest is influenced by other variables.